Usefulness of ENT clinical examinations in hospitalised patients chronically addicted to alcohol and tobacco to detect head and neck squamous cell carcinomas. A retrospective study of 159 patients - Baert, Maxime; Pascual, Caroline; Biet‐Hornstein, Aurélie; Nadjingar, Ritoungarte; Haremza, Céline; Page, Cyril (Clinical otolaryngology, 2019)
Objective To determine whether an ENT clinical screening examination done on all patients chronically addicted to alcohol or tobacco would allow the early diagnosis of cancer of the upper aerodigestive tract. Study Design Case series with chart review. Setting Non‐university general hospital. Subjects and methods A total of 159 patients presenting chronic addiction to alcohol or tobacco hospitalized in an addiction center or a comprehensive medical clinic were included in this study covering the period 2011‐2016. All patients systematically benefitted from an ENT clinical examination to detect mucous membrane lesions. The lesions were categorized as: cancerous, pre‐cancerous, or benign. The patients were divided into two groups for comparison: 1) patients with symptoms (dysphagia, dysphonia, dyspnea upon inhalation, cervico‐facial pain, secondary otalgia, pharyngeal discomfort unrelated to deglutition, presence of a cervical swelling, or weight loss), and 2) asymptomatic patients. Results The ENT exam was normal in 121 patients (76.1%). Fifty‐two patients (32.7%) had at least one symptom. The ENT exam allowed us to detect a benign lesion in 11 patients, a pre‐cancerous lesion in 11 patients, and a cancer in 16 (13.22%) patients. All patients with cancer had at least one symptom. Conclusion An ENT clinical screening examination done on patients chronically addicted to alcohol or tobacco can allow early diagnosis of cancer, particularly in patients with at least one symptom.